PENGELOLAAN DOKUMEN SARANA PRASARANA DAN ASET PADA SMP NEGERI XYZ JAKARTA - Damiyana, Damdam; Maulana, Muhammad Akbar (JURNAL LENTERA BISNIS, 2025)
Document management of infrastructure and assets is a crucial aspect in supporting operational and administrative efficiency at SMP Negeri XYZ Jakarta. However, the current practice still faces various obstacles, such as a manual recording system that is prone to errors, unorganized storage of physical documents, and limited human resource competency. These problems have an impact on inaccurate asset data, slow access to information, and obstacles in budget planning and auditing. This study aims to analyze the process of managing infrastructure and asset documents at SMP Negeri XYZ Jakarta, identify the obstacles faced, and formulate solutions for improvement. The research method uses a qualitative approach with data collection techniques through observation, interviews, and documentation studies. The results of the study indicate three main problems: (1) lack of trained human resources in document management, (2) vulnerability of physical documents to damage or loss, and (3) data discrepancies between documents and the real condition of assets. As a solution, this study recommends strategic steps such as: (1) regular training for asset management staff, (2) digitalization of documents by utilizing the SIMPAN BMN application and cloud storage, and (3) implementation of a barcode system and routine inventory to ensure data accuracy. The implementation of this solution is expected to improve transparency, efficiency, and accountability of school asset management.